DAMPAK EKONOMI DAN SOSIAL BADAN USAHA MILIKI DESA (BUMDES) SYARIAH KEMBANG SETANJUNG TERHADAP KESEJAHTERAAN MASYARAKAT DESA TANJUNG MEDAN - Las Utami (Jurnal Ilmiah Cano Ekonomos, 2023)
The initial goal of establishing a Village Owned Enterprise (BUMDes) is intended to encourage or accommodate all activities to increase community income. The management of BUMDes Ijen Lestari in the economic and social fields has a positive impact on the village economy. The purpose of this study was to determine the economic and social impact of the Kembang Setanjung Village-Owned Enterprise (BUMDes) on the welfare of the people of Tanjung Medan Village. The research approach used is a quantitative approach to the type of descriptive research. The research instruments used were observation, interviews and questionnaires. The subjects of this study were the village head of Tanjung Medan, the director of BUMDes Syariah Kembang Setanjung and the Tanjung Medan Village Community. Data analysis technique using IBM SPSS 23 software using multiple linear regression with a significance level of 5%. As for the number of samples of this study as the object of research as many as 200 respondents. The results of the study show that first, the economic impact of the Kembang Setanjung Village Owned Enterprise (BUMDes) on the welfare of the people of Tanjung Medan Village has a with a calculated significance value of 0.032 and less than 0.05 and t count (2.212) > t table (1.6787) which means that the economic hypothesis has a significant influence on social welfare is accepted. Second, the social impact of the Kembang Setanjung Syariah Village Owned Enterprise (BUMDes) on the Welfare of the Community of Tanjung Medan Village has an effect with a calculated significance value of 0.000 and smaller than 0.05 and t count (5.811 > t table (1.6787) which means that the social hypothesis has an influence significantly to the Welfare of society is accepted.